Typification of the name Rubus styriacus (Rosaceae) - Király, Gergely (Phytotaxa, 2017)
Rubus Linnaeus (1753: 492) ser. Micantes Sudre (1908: 16) is a series of intermediate taxonomic position, including species originating via the hybridization of glandular and non-glandular bramble biotypes (Holub 1992, Weber 1995). The number of species in this series is approximately 60; their distribution centre is in central and north-western Europe (Kurtto et al. 2010). The east-central European representatives of the series (ca. 15 species) are well known, both their taxonomy and distribution seem to be clarified due to recent investigations (Holub 1995, Weber 1995, Maurer & Drescher 2000, Matzke-Hajek 2004, Zieliński 2004, Király et al. 2014), and practically all species occurring in this region (excluding Rubus styriacus Halácsy 1890: 432) have satisfactorily been typified (Weber 1991, 1998, Király et al. 2013, 2015). However, even the lack of the typification of R. styriacus indicates unresolved questions; thus, the aim of this correspondence is the circumscription its original material and the typification of the name.